2021
DOI: 10.1128/aem.02082-20
|View full text |Cite
|
Sign up to set email alerts
|

Macrobdella decora : Old World Leech Gut Microbial Community Structure Conserved in a New World Leech

Abstract: Leeches are found in terrestrial, aquatic, and marine habitats on all continents. Sanguivorous leeches have been used in medicine for millennia. Modern scientific uses include studies of neurons, anticoagulants, and gut microbial symbioses. Hirudo verbana, the European medicinal leech, maintains a gut community dominated by two bacterial symbionts, Aeromonas veronii and Mucinivorans hirudinis, which sometimes account for as much as 97% of the total crop microbiota. The highly simplified gut anatomy and microbi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 85 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Blood-feeding invertebrate species had a significantly lower microbiome diversity (average Shannon index for each species was 0.5–1.5, at the 99% similarity 16S rRNA gene level; Supplementary Table S1 ) compared to non-blood-feeding invertebrates, swabs of fish prey species, and surrounding seawater (average Shannon index of 1.9–2.5; ANOVA p < 0.0001). In past studies, comparatively lower microbial diversity has been observed for other OBF taxa, including the freshwater leech genera Macrobdella and Hirudo ( Graf et al, 2006 ; McClure et al, 2021 ). One exception in this study was the copepod Lernanthropus with a slightly higher diversity (average Shannon index of 1.8 ± 0.4; Supplementary Table S1 ), comparable to the least diverse environmental sample.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Blood-feeding invertebrate species had a significantly lower microbiome diversity (average Shannon index for each species was 0.5–1.5, at the 99% similarity 16S rRNA gene level; Supplementary Table S1 ) compared to non-blood-feeding invertebrates, swabs of fish prey species, and surrounding seawater (average Shannon index of 1.9–2.5; ANOVA p < 0.0001). In past studies, comparatively lower microbial diversity has been observed for other OBF taxa, including the freshwater leech genera Macrobdella and Hirudo ( Graf et al, 2006 ; McClure et al, 2021 ). One exception in this study was the copepod Lernanthropus with a slightly higher diversity (average Shannon index of 1.8 ± 0.4; Supplementary Table S1 ), comparable to the least diverse environmental sample.…”
Section: Resultsmentioning
confidence: 94%
“…For Branchellion , an undescribed gammaproteobacteria and betaproteobacteria co-occurred with Vibrio , each comprising ~15%–17% of recovered ribotypes ( Figure 2 ; Supplementary Table S3 ). The maintenance of a gut community dominated by only 2–3 bacterial taxa has been observed for both Macrobdella and numerous hirudinid leeches ( Graf et al, 2006 ; Kikuchi and Graf, 2007 ; Laufer et al, 2008 ; McClure et al, 2021 ). Many of the undescribed secondary bacterial ribotypes associated with the marine OBF taxa were dissimilar from known bacteria (< 90% 16S rRNA gene identity; Supplementary Figure S2 ), thus likely representing novel taxa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Plesiomonas shigelloides is a Gram-negative, facultative anaerobe belonging to the family Enterobacteriaceae and is commonly found in brackish and freshwater ecosystems ( 1 , 2 ). While P. shigelloides is a known opportunistic animal and human pathogen ( 2 ), its role in the medicinal leech is unknown ( 3 8 ). The gut microbiomes of sanguivorous leeches are hypothesized to be critical for maintaining host fitness and overcoming challenges of feeding exclusively on blood ( 9 , 10 ).…”
Section: Announcementmentioning
confidence: 99%
“…Compared with vertebrates, leeches and other annelids are regarded as the beginning of senior invertebrates, with a complex digestive system and circulatory system replaced by a haemocoelomic system (Mayr, 1969 ). Although reports have focused on the gut microbiota of several species of leech, including Hirudo verbena , Hirudo orientalis , Hirudo medicinalis , Hirudo nipponia Whitman , and Poecilobdella manillensis , little is known about the linkage of gut microbes with the tissue homeostasis and fitness of the host (Graf et al, 2006 ; Laufer et al, 2008 ; Maltz et al, 2014 ; McClure et al, 2021 ; Meng et al, 2022 ; Neupane et al, 2019 ; Shi et al, 2021 ; Whitaker et al, 2014 ; Worthen et al, 2006 ). Recently, Drosophila melanogaster and Caenorhabditis elegans have been cited as excellent models for investigating the genetic underpinnings of host–microbiota, which implies that the physiological regulation of gut microbes is equally important in primeval animals (Dierking & Pita, 2020 ; Lee & Lee, 2014 ).…”
Section: Introductionmentioning
confidence: 99%